AQUI ELES SÃO MUITO DESCONFIADOS” LETRAMENTOS, IDENTIDADES E EDUCAÇÃO DO CAMPO - Santos, Simone Carvalho do Prado dos (2013)
This study aims to discuss the teaching of Portuguese in a school in the Field education context, the school is situated in a rural settlement linked to the Landless Movement in Paraná – Brazil, and the discussion is proposed from the local identities (HALL, 2003; BAUMAN, 2005; SILVA, 2000; MOITA LOPES, 2003) and their reflexes on the literacy (STREET, 1995; KLEIMAN, 2005, 2007; SOARES,2011; ROJO, 2009; BUNZEN, 2010) practices developed in the classroom under study. The teacher‟s perceptions (TELLES, 2009; FERREIRA, 2006, 2009; LIBERALI e MAGALHÃES, 2009; KLEIMAN e MARTINS, 2007; CELANI, 2009, GIL, 2005) and understanding about the environment where she works establishes some closeness or distance from the objectives planned for the subject, therefore, the reflection and the knowledge about the field social reality along with the critical literacy practice might produce better results, both in relation to the subject Portuguese and to the construction of positive identities inside this literacy agency: school. The urban-centric culture reflected on the school literacy practices, legitimated all the time both by the teacher‟s posture and the school material approach tends to marginalize the field culture and its representatives, interfering on the foreseen appropriation of knowledge, promoting some distance, which is possible to see through the results such as the SAEB – Sistema de Avaliação da Educação Básica (Basic Education Evaluation System in Brazil), which places the field population in great disadvantage in relation to the city population. The field research was carried out in a Field School opened in 2011 inside a rural settlement, linked to the Landless Movement, in Paraná State. Since it is a school at the beginning of its activities, it was possible to verify the staff efforts to initiate some reflection on the particularities of this education environment. The participants of the study are students in the 9th year – eleven students -, the teacher of Portuguese, the principal and the coordinator of the school. This is qualitative research developing an ethnographic case study. The results point out a great effort of the groups involved in the creation of official documents, such as the Field Education Guidelines/PR, among others, however, the effects of these discussions remain still limited while pointing to a more critical vision: this is a transition moment. The literacy practices observed tend to reproduce the school material and disregard the field environment and its particularities. As a contribution to the group involved in the research, a didactic sequence was developed together with the teacher of Portuguese and the school principal which approaches local themes in a conflicting and critical way.